Identifikasi Permasalahan Sosial Ekonomi Masyarakat dalam Pembangunan Jembatan Suramadu - Hakim, Andri; Santoso, Pradoto Iman (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
The Social Economic Change that together with Suramadu bridge development could happen as "social economic change" or "planned change", but also could happen as the social economics change that was not planned (unplanned change), like the emergece of the community's conflict, criminality, the anarchist, plundering as resulting from social jealousy etc.The identification of the social problem of economics relly was needed as the efforts to minimize the impact of the negative resulting from the social economics change in process of development. This article had a purpose to identify the social economics problems in the development of Suramadu bridge that related to community welfare. This article was useful to give the description and input to stakeholders that was related handling alternative that must be studied further.